2014
DOI: 10.1097/ccm.0b013e3182a643bc
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Recovery From Profound Accidental Hypothermia After 5 Hours of Cardiopulmonary Resuscitation

Abstract: With no evidence of trauma or asphyxia, profound accidental hypothermia with cardiac arrest represents a specific condition for which successful neurologic recovery is feasible despite prolonged cardiopulmonary resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 16 publications
0
30
0
2
Order By: Relevance
“…28,29 Many studies have found an association between poor outcome and coagulation disorders after hypothermia and severe trauma. 14,30 In our data, there was an association between coagulation disorders and survival, with a trend toward a lower prothrombin ratio and longer ACT in patients with traumatic injuries.…”
Section: Biological Parametersmentioning
confidence: 49%
“…28,29 Many studies have found an association between poor outcome and coagulation disorders after hypothermia and severe trauma. 14,30 In our data, there was an association between coagulation disorders and survival, with a trend toward a lower prothrombin ratio and longer ACT in patients with traumatic injuries.…”
Section: Biological Parametersmentioning
confidence: 49%
“…4 Low core temperature causes decrease in basic metabolism and neurologic function, 5 which in terms of cardiac arrest can have neuroprotective effect. Although SCA in case of severe hypothermia can lead to survival with good neurologic outcome, [6][7][8][9] prolonged cardiac arrest results in hypoxic brain injury and severe neurological dysfunction. 10 It is crucial to initiate effective chest compressions to maintain minimal cerebral blood flow.…”
Section: Resultsmentioning
confidence: 99%
“…Metoda ta jest w niektórych ośrodkach preferowaną formą ogrzewania pozaustrojowego, gdyż zmniejsza ryzyko wystąpienia opornej na leczenie niewydolności krążeniowo--oddechowej, często występującej po ogrzewaniu [16][17][18][19][20][21][22][23].…”
Section: Wstępunclassified